Síntesis de películas delgadas del compuesto ternario CuSbS2 depositadas por la técnica de electrodeposición para su uso como capa activa (2020)
This project focuses on developing a new material with thin film technology and with the characteristics of being a ternary compound, with a calcostibite phase and an orthorhombic crystalline structure, such as the CuSbS2 compound, since it has the necessary qualities to function as an active layer. of a solar cell. For the development of this compound, first a preliminary study of the electrodeposition technique of the Antimony and Copper elements was carried out on each Molybdenum substrates and after having the key parameters, the due simultaneous electrodeposition was carried out, which consists of depositing the antimony and Copper on Molybdenum substrates at the same time. For deposition using this method, parameters such as voltage, temperature of the electrolyte solution, concentration of Antimony and Copper salts, current pulses (PDC), the use of a complexing agent and the deposition time were evaluated. simultaneous.